A concerted transfer hydrogenolysis : 1,3,2-diazaphospholene-catalyzed hydrogenation of N=N bond with ammonia-borane - Chong, Che Chang (2014)
1,3,2-diazaphospholenes catalyze metal-free transfer hydrogenation of a N=N double bond using ammonia–borane under mild reaction conditions, thus allowing access to various hydrazine derivatives. Kinetic and computational studies revealed that the rate-determining step involves simultaneous breakage of the B-H and N-H bonds of ammonia–borane. The reaction is therefore viewed as a concerted type of hydrogenolysis.